Smart Lighting System for Library Using IoT Technology - Chitra, Batumalai; Xin, Rou Kong; Malathy, Batumalay (INTI International University, 2019)
Libraries in Universities and College utilize the traditional lighting systems need the switch to have the control of lighting. This will cause unnecessary waste of electricity. Therefore, a system that promotes efficient energy usage by automatic controlling the light in the library using Internet of Things (IoT) technology is proposed in this paper. The system uses Arduino with motion sensor to detect the motion of human to control the lights for particular areas in the library. This system enable organization to have a better lighting management for library and improve the efficiency of energy. This creates a more environment friendly and provides convenience to an organization by using this system.